Upaya Peningkatan Kemampuan Menulis Puisi dengan Metode Sugesti Imajinasi dan Media Audiovisual - Rohana, Rohana; Permanasari, Dian; Salsabilla, Martinia Putri (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
Writing poetry is not as easy as reading existing works. With the problems in the field, the purpose of this study is how this method improves students' skills in writing poetry and changes their behavior after being applied. The research method uses the classroom action research method or PTK. The use of classroom action research is carried out with planning, implementation, observation, and reflection. The aim is to determine the increase in the ability to write poetry with the method of imagination suggestion and audiovisual media. The results of this study are, with planning, observation, action, and reflection held in cycles I and II. The average value obtained in cycle I was 73.1 and increased by 82.3.